Using vegetation index to evaluate vegetation dynamics and its correlation with erosion processes (Revista Espinhaço, 2024)
The Normalized Difference Vegetation Index (NDVI) is used to identify the biophysical characteristics of vegetation. In this sense, the study's main objective was to assess changes in vegetation in a sub-basin of Gouveia, Minas Gerais (years 1984 and 2016). Evidence suggests that the shift in local vegetation cover may have favored erosive processes in the region. Landsat 5-TM and 8-OLI images were used over an 8-year interval from 1984 to 2016. The results were divided into four classes, according to field campaigns: (i) Non-vegetated area, (ii) Herbaceous vegetation, (iii) Non-forest natural formation, and (iv) Forest. The gullies occurring in the study area were surveyed and spatialized, accounting for 82 (in 1984) and 107 gullies (2016). The findings indicate growth in areas covered by herbaceous vegetation and non-vegetated areas. The region's monitoring by the NDVI index showed a variation in vegetation over the years studied, with the intensification of the development of gullies, which require the implementation of erosion mitigation techniques in the area.
Keywords: Gully; Landsat; Linear erosion; NDVI